A corpus-based cognitive analysis of metaphors of gender issues in national media - Fatim, Al Lastu Nurul; Hamid, M. Abdul; Mubasyiroh, Mubasyiroh (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
The identification of conceptual metaphors of gender issues in the national media using corpus linguistic analysis has constructed a discourse based on the correlation between experience and linguistic feature phenomena. This research identifies and reveals three conceptual metaphors based on word frequency, collocation, and concordance. A combined method with an explanatory sequential design was used by collecting Koran Sindo news in 2022–2023 that represented gender issues; there were 210 news articles with 71,920 words. Data collection techniques are documentation, listening, and note-taking using data analysis in AntConc and interactive models. The results of this study are as follows: first, the highest frequency of words is significantly found in the words 'korban' and 'perempuan.' Secondly, collocations have a contradictory tendency to present gender issues. Third, concordance produces identifying forms of conceptual metaphors, such as: a) 4 structural metaphors, conceptually meaning sexual coercion, rape, provider power, and necessity; b) 2 orientational metaphors have conceptual meanings, such as urgency and period; c) 3 ontological metaphors with conceptual meanings include deterioration, qualification, and capacity. This research contributes to exploring cognitive semantic prosody through the phenomenon of lexical and linguistic features.